Real-world changes in US health system hospital-based services following treatment with a prescription digital therapeutic for opioid use disorder. Issue 5 (20th October 2021) - Velez, Fulton F; Colman, Sam; Kauffman, Laura; Anastassopoulos, Kathryn; Murphy, Sean; Maricich, Yuri
ABSTRACT: Outcomes associated with buprenorphine therapy for the treatment of opioid use disorder (OUD) are suboptimal. reSET-O is an FDA-authorized prescription digital therapeutic (PDT) delivering neurobehavioral therapy via mobile devices to patients with OUD treated with buprenorphine. This analysis evaluated the net impact of reSET-O on medical costs among actively-engaged reSET-O patients using real-world observations. This real-world retrospective analysis of health care claims between October 2018 and October 2019 evaluated health care resource utilization up to 6 months before and 6 months after the initiation of a reSET-O prescription after accounting for the subset of patients not continuing on therapy after week 1 (non-engaged patients). Repeated-measures negative binomial models compared incidences of hospital-based encounters/procedures adjusted for days in each period as well as associated costs. The number needed to treat (NNT) to avoid an inpatient visit was calculated. Of the 351 patients who were prescribed reSET-O, 321 met the criteria of active engagement. Treatment with reSET-O was associated with a substantial reduction in medical costs of -$765, 450 (-$2, 385/patient, $235/patient greater than a previous analysis in which non-engaged patients were included) in the 6-month period after initiation. The gross reSET-O prescription cost of $584, 415 ($1, 665/patient) was substantially offset by $49, 950 ($142.31/patient) in refunds to payers. The medical cost reduction in engaged patients offset the cost of the therapeutic resulting in an overall cost reduction of -$230, 985 in this cohort (net savings of -$720 per patient). The number needed to treat to avoid an inpatient visit was 4.8. Engagement and continued treatment with reSET-O in patients with OUD treated with buprenorphine is associated with substantial real-world reductions in medical costs in the 6-month period following the initiation of the reSET-O prescription.